Estimación de cambios temporales de la condición corporal del borrego cimarrón (Ovis canadensis weemsi) a partir de fotointerpretación - Guerrero-Cárdenas, Israel; Alvarez-Cárdenas, Sergio; Gallina, Sonia; Corcuera, Pablo; Romero-Figueroa, Guillermo; Lozano-Cavazos, Eloy Alejandro; Tovar-Zamora, Ivonne; Guerrero-Tovar, Iker Yvan (Instituto de Ecología, A.C., 2020)
From a five-point scale as a non-invasive method, images obtained by photo trapping were analyzed, to visualize body parts (spine, ribs and hip) of the sheep, and to detect seasonal changes in the male and female body condition, evaluating the consumption of protein, obtained from content in the forages. Twenty camera traps were used, particularly located in surface water bodies. One hundred ninety-nine animals were identified in the two years of sampling; 120 in 2010 and 79 in 2011. Regarding the score scale, a greater number of individuals were found in categories C3 (moderate, n = 109), C2 (bad, n = 44), C4 (good, n = 32) and with the smallest number C5 (excellent, n = 9) and C1 (very bad, n = 5). A positive correlation was observed between the categories of body condition and protein consumption (r = 0.40, P < 0.05). Crude protein was the most important explanatory variable, positively related to body condition categories (R2 = 0.166, F = 38.8, P < 0.0001) of sheep. In general, sheep were observed in intermediate categories of body condition (C3). Females found themselves in the categories of very bad, bad and moderate. The males found themselves in moderate, good and excellent body condition. This method allowed to visualize and analyze the body condition of the sheep at different times, being possible to use them as a tool to detect changes in the natural habitat (quantity and quality of the forage) and apply it as an alternative method within the management and conservation strategies of the natural populations of sheep bighorn.